Students’ responses to tutor feedback: focusing on their writing and perceptions - Cho, Sookyung; Park, Chanho (Penerbit Universiti Kebangsaan Malaysia, 2019)
Studies on students’ responses to tutor feedback have been conducted in large scales, in particular, focusing on students’ perceptions of tutor feedback. However, few of these studies have examined how students respond to tutors’ written feedback in their writing. In order to broaden the understanding of a student’s response to a tutor’s feedback, this study examines tutors’ written feedback, students’ writings, and their perceptions of the feedback. Based on this examination, this study aims to see what types of tutor feedback do students incorporate in their revisions and what the students think of tutor feedback. The participants were 11 tutors and 18 college students. Each student received tutor feedback on two writing assignments—a compare-and-contrast essay and an argumentative essay— and filled out a questionnaire that asked about their experiences with the feedback they received. The analysis of students’ writing and tutor feedback reveal that error type and feedback type seem to affect a student’s incorporation of feedback; in particular, students incorporated content-oriented, indirect, and coded types of feedback more than the other feedback types. The questionnaire data show that most students valued the tutor feedback; however, low incorporators had more problems in incorporating tutor feedback. Based on these results, suggestions on tutor feedback and implications for future studies are discussed.